Respuesta :

Answer:

1: 11

2: 1

3: -9

4: -49

Answer:

See screenshot below

Step-by-step explanation:

  1. All you have to do it substitute the x in the rule with the x in the table. Let's do the first one in the steps below.
  2. Write the equation with the x value: y = -10(-1) + 1
  3. -10 × -1 = 10
  4. Plug 10 in: y = 10 + 1
  5. 10 + 1 = 11
  6. So, y = 11
  7. Now that you know how to find the rest, go ahead and do it (my answer doesn't show the work, but the answers are in the screenshot below)

I hope this helps!

Ver imagen capsasha2